Synapse organization and modulation via C1q family proteins and their receptors in the central nervous system. (March 2017) - Matsuda, Keiko
Highlights: A new category of synapse organization is mediated by members of the C1q/tumor necrosis factor (C1q/TNF) superfamily proteins. Synapse formation achieved by a molecular bridge linking postsynaptic GluD2 and presynaptic neurexins via Cbln1. C1ql2/3 directly bind to amino-terminal domain of kainate receptor. Neurexin3 binds C1ql2/3 via the sequence encoded by exon 25b. C1ql2/3 serve as master regulators of postsynaptic kainate receptor complexes in CA3 neurons. Abstract: Several C1q family members, related to the C1q complement component are extensively expressed in the central nervous system. Cbln1, which belongs to the Cbln subfamily of C1q proteins and released from cerebellar granule cells, plays an indispensable role in the synapse formation and function at parallel fiber–Purkinje cell synapses. This is achieved by formation of a trans-synaptic tripartite complex which is composed of one unit of the Cbln1 hexamer, monomeric neurexin (NRX) containing a splice site 4 insertion at presynaptic terminals and the postsynaptic GluD2 dimers. Recently an increasing number of soluble or transmembrane proteins have been identified to bind directly to the amino-terminal domains of iGluR and regulate the recruitment and function of iGluRs at synapses. Especially at mossy fiber (MF)–CA3 synapses in the hippocampus, postsynaptic kainate-type glutamate receptors (KARs) are involved in synaptic network activity through their characteristic channel kinetics. C1ql2 and C1ql3, which belong to the C1q-like subfamily of C1q proteins, are produced by MFs and serve as extracellular organizers to recruit functional postsynaptic KAR complexes at MF–CA3 synapses via binding to the amino-terminal domains of GluK2 and GluK4 KAR subunits. In addition, C1ql2 and C1ql3 directly bind to NRX3 containing sequences encoded by exon 25b insertion at splice site 5. In the present review, we highlighted the generality of the strategy by tripartite complex formation of the specific type of NRX and iGluR via C1q family members.